Analisis Hukum terhadap Tanggungjawab Perusahaan Pemberi Izin Kapal Asing Sandar di Pelabuhan pada PT. Pelni Cabang Lhokseumawe - Rahalim Raja Muda Harahap; Taufik Siregar; Rizkan Zulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The problem in this research is how the legal arrangements regarding the granting of permits for foreign ships that will dock at ports in Indonesia, how the process of granting permits for foreign ships that will dock at the Port of Lhoksumawe and what are the constraints and responsibilities of PT. Pelni Lhoksumawe Branch in granting permits for foreign ships that will dock at the port. This type of research is directed to normative juridical law research. The nature of the research used in completing this thesis is descriptive analysis. Data collection techniques are carried out through: Library Research: namely by collecting and studying and analyzing concepts, theories, opinions or findings and statutory provisions related to law. Field research (Field Research), namely by conducting direct field research to obtain data such as interviews. In this case the researchers directly conduct research to PT. Pelni Lhoksumawe Branch which handles the port for foreign ships that will dock. Analysis of the data used in this study is to use qualitative methods.